2010
DOI: 10.1111/j.1467-9523.2010.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Power, Positionality and the View from within: Agricultural Advisers' Role in Implementing Participatory Extension Programmes in the Republic of Ireland

Abstract: This article examines the experience of implementing a participatory model of public extension advisory programme in the Republic of Ireland. Focusing specifically on the role and experiences of extension advisers, it draws evidence from an evaluation of the 'Options for Farm Families Programme'. It is argued that, while participatory approaches are increasingly promoted from an institutional perspective, they also raise a number of dilemmas for extension advisory staff that are ultimately damaging to the oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 20 publications
2
20
0
4
Order By: Relevance
“…It can therefore be argued that relatively loosely planned interaction assignments can, at least in part, be beneficial because they offer opportunities to reflect-in-action (cf. Forester 1999;Bergeå and Ljung 2007;Stenseke 2009;Mahon et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can therefore be argued that relatively loosely planned interaction assignments can, at least in part, be beneficial because they offer opportunities to reflect-in-action (cf. Forester 1999;Bergeå and Ljung 2007;Stenseke 2009;Mahon et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…One factor the officers mentioned was inadequate allocation of time and other resources for the SCSI's local operations and for maintaining satisfactory levels of stakeholder contact. Limited resource allocation seems to be a common problem in participatory undertakings (see e.g., Lowndes et al 2001;Senecah 2004;Mahon et al 2010). Some interview statements indicated that in the SCSI's case it was a matter of priority, and mirrored a certain lack of recognition within the organization of the role stakeholder interaction played in achieving the agency's objectives.…”
Section: Discussionmentioning
confidence: 99%
“…Private sector planners also provide extension services. Since the mid-1990s, Teagasc has moved towards a model of participatory extension which sees farmers as full collaborators in research and extension (Mahon et al, 2010). One such form of extension is that of discussion groups, which consist of a group of local farmers who meet regularly on farms to see, discuss and learn about technologies and practices that may be applied on their own farms.…”
Section: Agricultural Extension Services and Outputmentioning
confidence: 99%
“…This paper connects to an observation by Birner et al (2009) that in the analysis of extension system reform and the discussion on 'best-fit' extension systems political economy aspects should not be underestimated, an issue which has been addressed by a number of papers in recent years (Parkinson 2009;Mahon, Farrell, and McDonagh 2010;Berhanu and Poulton 2014). In their paper, Diesel and Miná Dias analyze the implementation of a nationwide extension program focused on an agro-ecological transition and endogenous development, delivered decentrally through state-civil society partnerships.…”
mentioning
confidence: 55%